Faktor-Faktor yang Mempengaruhi Nilai Perusahaan (Studi Empiris Pada Perusahaan Di Sektor Non-Cyclical, BEI) - Prasetyo, Irwanto; Prawidya, Afara Ross (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2023)
This research aims to demonstrate how independent variables such as profitability, liquidity, capital structure, firm size, and dividend policy impact or relate to the dependent variable, firm value. It utilizes annual financial ratio analysis of non-cyclical sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The secondary data processed in this study were obtained from the Indonesia Stock Exchange (IDX) and relevant company websites. A purposive sampling method was employed in this research. The data analysis method used was multiple linear regression analysis. The results of the analysis indicate that profitability, liquidity, capital structure, and dividend policy variables have a significant positive influence both simultaneously and partially on the value of non-cyclical sector companies. However, the firm size variable shows no significant influence both simultaneously and partially on the value of non-cyclical sector companies.